Environmental risk assessment : a toxicological approach - Simon, Ted (CRC Press, Taylor & Francis Group, 2020)
"This book explains how environmental risk assessment in particular is of increasing importance as a means of seeking to address the potential effects of chemicals in the environment in both the developed and developing world"-- Provided by publisher
Keywords: Environmental risk assessment.; Environmental toxicology.; Environmental monitoring.; Risk assessment.; elektronické knihy; electronic books